Effect of Classcraft-Based Gamification on Strengthening the Disciplinary Character of Elementary School Students - Ahmad Suryadi; Arie Rakhmat Riyadi; Yulianti Fitriani (Journal of Indonesian Primary School, 2026)
Character education in the digital era challenges educators to find innovative ways to cultivate student discipline without relying on conventional, punitive measures. While gamification has emerged as a viable pedagogical tool, empirical evidence regarding the specific impact of immersive behavioral gamification platforms, such as Classcraft, on young learners' disciplinary character remains scarce. This study aims to investigate the effect of Classcraft-based gamification on strengthening the discipline character of elementary school students. Utilizing a quantitative approach with a quasi-experimental design, this research involved 30 upper-grade students (grades 5 and 6) from SD Negeri Padasuka Baros Serang, equally divided into an experimental group (n = 15, utilizing Classcraft) and a control group (n = 15, utilizing conventional classroom management). Data on students’ disciplinary behavior were systematically collected through structured observation techniques and analyzed using descriptive and inferential parametric statistics (independent and paired-sample t-tests).The findings revealed that Classcraft-based gamification has a highly positive and statistically significant effect on enhancing students' discipline character. Within the experimental group, discipline scores escalated dramatically from a pre-test average of 61.12 (low category) to a post-test average of 93.14 (very high category). Furthermore, the experimental group’s post-test performance (M = 92.34) significantly outperformed the control group (M = 65.61, low category) with an inferential significance value of p < 0.000. These results indicate that Classcraft’s role-playing mechanics successfully transform rigid rules into engaging, collaborative quests that internalize intrinsic discipline. Consequently, this study provides critical empirical support for leveraging digital gamification as a non-coercive, preventive alternative to mitigate behavioral issues in primary education.